An analysis of X-factor, triple X-factor, and the center of pressure (cop) according to the feel of the golf driver swing - Kim, Y.-S.; So, J.-M. (Korean Journal of Sport Biomechanics, 2016)
Objective: The aim of this study was to analyze X-factor, triple X-factor, and the center of pressure (COP) according to the feel of golf driver swing. Method: For this research, 9 golfers from the Korea Professional Golfers' Association (age: 30.11±2.98 yrs, height: 178.00±8.42 cm, weight: 76.22±8.42 kg, experience: 10.06±3.11 yrs) were recruited to participate in the experiment. Twelve Motion Analysis Eagle-4 cameras were installed and an image analysis was conducted by using the NLT (non-linear transformation) method, and 2 units of Kistler type 5233A dynamometer were used to measure ground reaction force. The sampling ratio was set at 1000 Hz. The golfers each took 10 swings by using their own driver, and chose the best and worse feel from among 10 shots. A paired-sample t-test was used to analyze the results. Results: In regard to feel, no change in head speed, X-factor, and the triple X-factor's X-factor stretch, hip rise, and head swivel, was observed (p>.05). Regarding ground reaction force, a difference was observed between the top of the backswing (p<.05) and impact (p<.05) in the vertical force of the left foot. For COP, a difference was also observed between the mid backswing (p<.001), late backswing (p<.001), and top of the backswing (p<.05) for the right foot X-axis and Y-axis mid follow through (p<.01). Conclusion: It can be reasoned that, irrespective of feel, the head speed, X-factor and triple X-factor's Xfactor stretch, hip rise and head swivel did not have an effect on drive distance for domestic golfers, and the vertical reaction force of the left foot and left-right movement span's pressure dispersal of the right foot had an increasing effect on drive distance.